A Critical Realist Approach on Autism: Ontological and Epistemological Implications for Knowledge Production in Autism Research - Kourti, Marianthi (Frontiers in Psychology, 2021)
The ontological status of autism has been a subject of considerable debate and philosophical approaches of it have been recent and sparse. On the one hand, from its conception, autism has been historically heavily located in the fields of psychiatry, psychology and neuroscience, which often assume access to an ‘objective’, neutral and infallible reality that is external to the research process and is based on the autistic person’s biology and behavioural characteristics, which can be scientifically observed and studied. On the other, proponents of the neurodiversity movement argue against medicalised and pathologising approaches to autism and towards approaches that consider social constructions of autism and relations of power. The Critical Realist philosophy can help reconcile the two positions. Critical Realism conceptualises objectivity as a statement about an object, rather than a neutral and infallible reality. Consequently, Critical Realism suggests that access to reality can only occur through fallible theories. It also suggests that effective theorising goes beyond appearances and phenomena and may even contradict them, which can help challenge dominant behaviourist approaches on autism. I then explore how the tenets of Critical Realism can help strengthen autistic-led theories of autism, the arguments they make, as well as how they support the importance of community autism knowledge. Finally, I present how Critical Realism’s approach to knowledge itself as well as the process of knowledge creation can strengthen autistic theorising, autistic participation in autism research and autistic emancipation. In the last part of the article, I explore how the concepts of Critical Realism apply to autistic sociability. I start with the debate between structure and agency, how Critical Realism reconciles this debate and the implications for autistic emancipation and autism research. I then present Critical Realism’s process of critique and explanation, how they connect to human emancipation and how they can lead to impactful change in autism research by requiring clear links from research to practice, enhancing practices with strong theoretical underpinnings and thus aiding the aims of emancipatory autism research.